Natural Progression of Helicobacter pylori-Negative Gastritis with Lymphoid Follicles in Children: Prospective Evaluation and Outcome - Richter, Vered; Mendlovic, Sonia; Shalem, Tzipi; Eindor-Abarbanel, Adi; Shirin, Haim; Broide, Efrat (Turkish Journal of Gastroenterology, 2021)
Background: The association of Helicobacter pylori-negative gastritis with lymphoid follicles (LFs) in children is still unclear. Therefore,we aimed to investigate the natural history and significance of H. pylori-negative gastritis with LFs in children.Methods: We identified children with histologically proven H. pylori-negative gastritis with LFs between June 2014 and January 2017.The children were invited for a follow-up examination. The clinical, endoscopic, and histological findings of the index esophagogastroduodenoscopy(EGD) were revised and compared to the follow-up findings.Results: A total of 754 children underwent EGD. Among the 48 children diagnosed with H. pylori-negative gastritis, 17 (35.41%) hadgastric LFs. Eight agreed to participate in the study. The mean follow-up was 25.58 ± 4.52 (range, 20.53-35.73) months. Three childrenstill had histologic findings of chronic gastritis with LFs. Four children had resolution of the gastritis but still had LFs, and 1 patient hadresolution of both the gastritis and LFs.Conclusion: LFs were still present in children with H. pylori-negative gastritis after a mean follow-up of 2 years, and in some children,despite resolution of the gastritis. Therefore, this histological finding might be a non-pathological feature in children and does not needany contribution or follow-up.